2012
DOI: 10.1186/1748-717x-7-114
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography-guided permanent brachytherapy for locoregional recurrent gastric cancer

Abstract: BackgroundLocoregional recurrence is the typical pattern of recurrence in gastric cancer, and cannot be removed by surgery in most of the patients. We aimed to evaluate the feasibility and efficacy of computed tomography (CT)-guided brachytherapy for patients with locoregional recurrent gastric cancer.Materials and methodsWe reviewed the case histories of 28 patients with locoregional recurrent gastric cancer that were selected for CT- guided brachytherapy by a multidisciplinary team. The clinical data of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…125 I seed implantation is a minimally invasive, widely used treatment that has unique advantages in the treatment of locally advanced tumors ( 11 , 12 ). In the US, radioactive seed implantation has been used as the standard treatment for early prostate cancer ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…125 I seed implantation is a minimally invasive, widely used treatment that has unique advantages in the treatment of locally advanced tumors ( 11 , 12 ). In the US, radioactive seed implantation has been used as the standard treatment for early prostate cancer ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of brachytherapy in recurrent gastric cancer was demonstrated in a recent case series. Complete tumor response rate of 50% and partial response rate of 28.6% were achieved respectively . However, our experience with brachytherapy for gastric conduit cancer is limited.…”
Section: Discussionmentioning
confidence: 92%
“…To get a more comprehensive and reliable evaluation of effectiveness between RTDPTB and CCTB, several studies based on CCTB reported in the literature were also analyzed [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The relevant information was summarized in Table 6 .…”
Section: Discussionmentioning
confidence: 99%